Pengaruh Celebrity Endorser, Content Marketing dan Product Quality terhadap Purchase Intention - Aldi Gunawan; Rezi Muhamad Taufik Permana (UNISBA Press, 2024)
Abstract. This research aims to find out Celebrity Endorser, Content Marketing and Product Quality for Scarlett Whitening via Tiktok social media and to find out respondents responses regarding Celebrity Endorser, Content Marketing and Product Quality for Scarlett Whitening towards Scarlett Whitening's Purchase Intention via Tiktok social media. This type of research uses descriptive and verification methods using a quantitative approach by operating calculations using the IBM SPSS 26 program and sampling techniques using nonprobability sampling, precisely using purposive sampling. Then a sample of 250 respondents was obtained who met the criteria for having purchased Scarlett Whitening products and used the Tiktok application. The data analysis method in this research uses multiple linear regression analysis with the aim of finding out the direction of the relationship between the Celebrity Endorser ( ), Content Marketing ( ) and Product Quality ( ) with the Purchase Intention (Y). Thus, the results of this research show that Celebrity Endorser partially has no significant effect on Purchase Intention. Apart from that, Content Marketing partially has a significant effect on Purchase Intention. Then Product Quality partially has a significant effect on Purchase Intention. As well as the variables Celebrity Endorser, Content Marketing and Product Quality simultaneously have a significant effect on Scarlett Whitening's Purchase Intention via Tiktok social media. Abstrak. Penelitian ini bertujuan untuk mengetahui Celebrity Endorser, Content Marketing dan Product Quality pada Scarlett Whitening melalui media sosial Tiktok dan untuk mengetahui tanggapan responden mengenai Celebrity Endorser, Content Marketing dan Product Quality pada Scarlett Whitening terhadap Purchase Intention Scarlett Whitening melalui media sosial Tiktok. Jenis penelitian ini menggunakan metode deskripstif dan verifikatif dengan menggunakan pendekatan kuantitatif dengan mengoperasikan perhitungan menggunakan program IBM SPSS 26 dan teknik penarikan sampel menggunakan nonprobability sampling tepatnya menggunakan purposive sampling. Kemudian didapat sampel sebanyak 250 responden yang telah memenuhi kriteria pernah melakukan pembelian produk Scarlett Whitening dan menggunakan aplikasi Tiktok. Metode analisis data dalam penelitian ini menggunakan analisis regresi linear berganda dengan tujuan untuk mengetahui arah hubungan antara variabel Celebrity Endorser ( ), Content Marketing ( ) dan Product Quality ( ) dengan variabel Purchase Intention (Y). Dengan demikian didapatkan hasil dari penelitian ini bahwa Celebrity Endorser secara parsial tidak berpengaruh signifikan terhadap Purchase Intention. Selain itu Content Marketing secara parsial berpengaruh signifikan terhadap Purchase Intention. Kemudian Product Quality secara parsial berpengaruh signifikan terhadap Purchase Intention. Serta variabel Celebrity Endorser, Content Marketing dan Product Quality secara simultan berpengaruh signifikan terhadap Purchase Intention Scarlett Whitening melalui media sosial Tiktok.